Body mass and circumference of upper arm are associated with race performance in ultraendurance runners in a multistage race - The Isarrun 2006 - Knechtle, B.; Duff, B.; Welzel, U.; Kohler, G. (Research Quarterly for Exercise and Sport, 2009)
In the present study, we investigated the association of anthropometric parameters with race performance in ultraendurance runners in a multistage ultraendurance run, in which athletes had to run 338 km within 5 consecutive days. In 17 male successful finishers, calculations of body mass, body height, skinfold thicknesses, extremity circumference, skeletal muscle mass (SM), and percentage body fat (%BF) were performed before the race to correlate anthropometric parameters with race performance. A positive association was shown between total running time and both body mass (r2 = .29, p<.05)and upper arm circumference (r2 = .23, p < .05). In contrast, body height, skinfold thicknesses, extremity circumference, SM, and %BF showed no association with race performance (p > .05). We concluded that in a multistage ultraendurance run, body mass and upper arm circumference were negatively associated with race performance in well experienced ultraendurance runners. In contrast, body height, skinfold thicknesses, circumferences of the other extremities, SM, and %BF showed no association with race performance.